Cellular Immune Responses to Live Attenuated Japanese Encephalitis (JE) Vaccine SA14-14-2 in Adults in a JE/Dengue Co-Endemic Area. - Lance Turtle; Filippo Tatullo; Tanushka Bali; Vasanthapuram Ravi; Mohammed Soni; Sajesh Chan; Savita Chib; Manjunatha M Venkataswamy; Prachi Fadnis; Mansour Yaïch; Stefan Fernandez; Paul Klenerman; et al. (PLoS Neglected Tropical Diseases)
Background Japanese encephalitis (JE) virus (JEV) causes severe epidemic encephalitis across Asia, for which the live attenuated vaccine SA14-14-2 is being used increasingly. JEV is a flavivirus, and is closely related to dengue virus (DENV), which is co-endemic in many parts of Asia, with clinically relevant interactions. There is no information on the human T cell response to SA14-14-2, or whether responses to SA14-14-2 cross-react with DENV. We used live attenuated JE vaccine SA14-14-2 as a model for studying T cell responses to JEV infection in adults, and to determine whether these T cell responses are cross-reactive with DENV, and other flaviviruses. Methods We conducted a single arm, open label clinical trial (registration: clinicaltrials.gov NCT01656200) to study T cell responses to SA14-14-2 in adults in South India, an area endemic for JE and dengue. Results Ten out of 16 (62.5%) participants seroconverted to JEV SA14-14-2, and geometric mean neutralising antibody (NAb) titre was 18.5. Proliferation responses were commonly present before vaccination in the absence of NAb, indicating a likely high degree of previous flavivirus exposure. Thirteen of 15 (87%) participants made T cell interferon-gamma (IFNγ) responses against JEV proteins. In four subjects tested, at least some T cell epitopes mapped cross-reacted with DENV and other flaviviruses. Conclusions JEV SA14-14-2 was more immunogenic for T cell IFNγ than for NAb in adults in this JE/DENV co-endemic area. The proliferation positive, NAb negative combination may represent a new marker of long term immunity/exposure to JE. T cell responses can cross-react between JE vaccine and DENV in a co-endemic area, illustrating a need for greater knowledge on such responses to inform the development of next-generation vaccines effective against both diseases. Trial registration clinicaltrials.gov (NCT01656200).